2005
DOI: 10.1007/s00259-004-1741-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo uptake of [11C]choline does not correlate with cell proliferation in human prostate cancer

Abstract: In vivo uptake of [(11)C]choline does not correlate with cell proliferation in human prostate cancer as depicted by Ki-67. Our results suggest that a process other than proliferation is responsible for the uptake of [(11)C]choline in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 27 publications
3
47
2
4
Order By: Relevance
“…Similar to previous studies, no significant differences were observed when the SUV was related to PSA or to Gleason score (16,18,26,28), whereas other groups reported of significant correlation between SUV and PSA level (24,25). One of the potential utilities of [ 11 C]choline PET/CT in primary PCa could be to identify patients with more aggressive lesions to avoid sampling error and appropriately direct therapy for higher grade, riskier tumors.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to previous studies, no significant differences were observed when the SUV was related to PSA or to Gleason score (16,18,26,28), whereas other groups reported of significant correlation between SUV and PSA level (24,25). One of the potential utilities of [ 11 C]choline PET/CT in primary PCa could be to identify patients with more aggressive lesions to avoid sampling error and appropriately direct therapy for higher grade, riskier tumors.…”
Section: Discussionsupporting
confidence: 82%
“…No hitherto published prospective study of FEC-PET has suggested an association between PET parameters and the Gleason score. Initial [ 11 C]-choline-PET/CT studies with acquisition times starting from 5 to 10 minutes after injection, reported no such significant correlation (33,34). But supporting the present findings, a recently published study using […”
Section: Discussionmentioning
confidence: 99%
“…49 Vários mecanismos foram postulados como causadores da diminuição do SUV max após TSH: 1) redução do volume da lesão (com redução do sinal por efeito de volume parcial); 2) diminuição dos níveis de proliferação celular e, 3) sub regulação da expressão dos genes que regulam o metabolismo lípídico, incluindo menor actividade do transportador de colina ou da enzima colina quinase. [50][51][52][53][54][55] Contudo, em doentes resistentes à castração, a TSH parece não apresentar os mesmos efeitos.…”
unclassified